1996
DOI: 10.15448/1984-6746.1996.164.35918
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Greek Mathematico-Physical Paradox

Abstract: SfNTESE-Neste artigo revisa-se a literatura sobre paradoxos matemático-físicos gregos antigos. Trata-se de paradoxo de números irracionais, o dilema de Democritus, a antinomia de mudança, bem como os seguintes paradoxos de Zenon: a dicotomia, o Aquiles, os blocos móveis, o argumento contra a pluralidade, o dilema e a semente de painço. Palavras-chaves: Paradoxo, Matemática, Zenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The term paradox comes with a long history and multiple meanings that are influenced by the diverse disciplines the term has been in use such as philosophy, sociology, psychology, and anthropology (Lewis, 2000). According to the Oxford English Dictionary, a paradox is ‘a statement or tenet contrary to received opinion or expectation’ (Erickson & Fossa, 1998, p.147). However, it is indicated that this perceived absurdity or incongruence is essential but not sufficient to identify or label a paradox.…”
Section: The Notion Of Paradoxmentioning
confidence: 99%
“…The term paradox comes with a long history and multiple meanings that are influenced by the diverse disciplines the term has been in use such as philosophy, sociology, psychology, and anthropology (Lewis, 2000). According to the Oxford English Dictionary, a paradox is ‘a statement or tenet contrary to received opinion or expectation’ (Erickson & Fossa, 1998, p.147). However, it is indicated that this perceived absurdity or incongruence is essential but not sufficient to identify or label a paradox.…”
Section: The Notion Of Paradoxmentioning
confidence: 99%